Review of the leafhopper genus Penthimia Germar (Hemiptera: Cicadellidae: Deltocephalinae) from the Indian subcontinent with description of seven new species - Shobharani, M.; Viraktamath, C.a.; Webb, M.d. (Zootaxa, 2018)
Species of the leafhopper genus Penthimia Germar known from the Indian subcontinent are reviewed based on the examination of type specimens. Seven new species of the genus, Penthimia curvata sp. nov. (Karnataka: Bandipur), P. meghalayensis sp. nov. (Meghalaya: Nangpoh), P. neoattenuata sp. nov. (India: Tamil Nadu), P. ribhoi sp. nov. (India: Meghalaya), P. sahyadrica sp. nov. (Karnataka: Dharmasthala, Agumbe; Kerala: Thekkady), P. spiculata sp. nov. (Karnataka: Nagarahole) and P. tumida sp. nov. (Tamil Nadu: Ootacamund; Kerala: Munnar) are described. The following nomenclatorial changes are proposed: Penthimia alba Zahniser, McKamey & Dmitriev, 2012 (replacement name for P. thoracica Distant, 1918, nec Panzer, 1799), syn. nov. of P. quadrinotata Distant, 1918; Neodartus scutellatus Distant, 1908 syn. nov. of Penthimia ereba Distant 1908; P. nilgiriensis Distant, 1918 syn. nov. of P. montana Distant, 1918; P. scutellata (Distant) comb. nov. (from genus Neodartus); a lectotype is designated for P. maculosa Distant, stat. revived, thereby removing its synonymy with P. scapularis Distant. The following other lectotypes are designated: P. attenuata Distant, P. subniger Distant, P. scapularis Distant, P. distanti Baker, P. ereba Distant, N. scutellatus Distant, P. fraterna Distant, P. funebris Distant, P. juno Distant, P. maculosa Distant, P. montana Distant, P. noctua Distant, P. quadrinotata Distant, P. alba Zahniser, McKamey & Dmitriev. Examination of types of Penthimia rufopunctata Motschulsky revealed that it belongs to Penthimia and hence it is transferred back to that genus from Neodartus, revised placement. The following species previously included in the genus Penthimia are transferred to the genera Tambila Distant and Vulturnus Kirkaldy: Tambila badia (Distant) comb. nov., T. majuscula (Distant) comb. nov., T. vittatifrons (Distant) comb. nov., T. variabilis (Distant) comb. nov. and Vulturnus flavocapitata (Distant) comb. nov. Three species are treated in a new Penthimia compacta Walker complex, i.e., Penthimia compacta Walker 1851, Penthimia subniger Distant 1908 and Penthimia scapularis Distant 1908. All taxa are described and a key to Penthimiini genera found in the subcontinent and also a key to species of Penthimia are included.